Firms' Financial Performance in Age of Competitiveness: The Role of IT Governance - Anwar, Adnan; Qabool, Sahar; Aziz, Atif; Khan, Muhammad Kamran (iRASD Journal of Economics, 2022)
Over the past decade, fierce competition in the turbulent business environment has witnessed new business modifications. These new modifications have motivated organizations to deal with new challenges and business risks proactively. In the prevailing competitive environment, organizations' survival depends on adopting new business models and IT Governance. Firms with adaptability, resources, and motivation to adopt and implement new business models would have sustainable growth. Moreover, such firms would have leveraged against business risks and the potential to benefit from upcoming opportunities. The citation pearl growing method is used to analyze earlier studies for better insight into IT governance and lay down theoretical implications, practical implications and future directions for the policymakers and academicians.